High noon for Billy the Kid? (Economist, 1995)
Focuses on Microsoft as it faces an August 24, 1995 release date for the Windows 95 operating system and deals with a threat from the Justice Department that may stand in the way of this accomplishment. The Justice Department's opposition to Microsoft's merger with Intuit; Actions by Judge Stanley Sporkin; Other aspects.